Efficacy of Emotional Freedom Techniques (EFT) in Reducing Public Speaking Anxiety: A Randomized Controlled Trial - Jones, S.; Thornton, Jennifer; Andrews, Henry (Foundation for Epigenetic Medicine, 2011)
Thirty six volunteers with Public Speaking Anxiety (PSA) were randomly allocated into a treatment group and wait-list control group. Subjective self-report measures were taken before, during, and after a forty-five minute treatment session with Emotional Freedom Techniques (EFT). Behavioural observations were recorded during a 4-minute speech immediately after treatment. Comparisons between groups revealed significant reductions in PSA on all self-report measures, but not in behavioural observations. Changes in scores taken before and after treatment for each participant revealed significant reduction in PSA on all subjective and behavioural measures. A significant reduction in PSA as measured by Subjective Units of Discomfort was demonstrated within the first 15 minutes of treatment with EFT, with further significant reductions also demonstrated at 30 and 45 minutes. EFT was found to be a quick and effective treatment for PSA.